2012
DOI: 10.1007/978-3-642-33269-2_70
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Learning of Linguistic Hierarchy in a Multiple Timescale Recurrent Neural Network

Abstract: Abstract. Recent research has revealed that hierarchical linguistic structures can emerge in a recurrent neural network with a sufficient number of delayed context layers. As a representative of this type of network the Multiple Timescale Recurrent Neural Network (MTRNN) has been proposed for recognising and generating known as well as unknown linguistic utterances. However the training of utterances performed in other approaches demands a high training effort. In this paper we propose a robust mechanism for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Therefore, our knowledge of the hierarchical nature of linguistic structures and the theory of linguistic compositionality have been shown to be biologically plausible. Previous works have applied this hierarchical structure to RNNs in movement tracking (Paine and Tani, 2004), sensorimotor control systems (Yamashita and Tani, 2008) and speech recognition (Heinrich et al, 2012). Based on the above conclusions, we adopt the multiple timescales concept to implement the temporal hierarchy architecture for representing multiple compositionalities which will help in handling longer sequences for our CLM.…”
Section: Related Workmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, our knowledge of the hierarchical nature of linguistic structures and the theory of linguistic compositionality have been shown to be biologically plausible. Previous works have applied this hierarchical structure to RNNs in movement tracking (Paine and Tani, 2004), sensorimotor control systems (Yamashita and Tani, 2008) and speech recognition (Heinrich et al, 2012). Based on the above conclusions, we adopt the multiple timescales concept to implement the temporal hierarchy architecture for representing multiple compositionalities which will help in handling longer sequences for our CLM.…”
Section: Related Workmentioning
confidence: 95%
“…In order to improve the performance of the CLMs, there is a need for better representation of the additional levels of compositionality and the richer discourse structure found in CLMs. Heinrich et al (2012) used multiple timescale RNNs to learn the linguistic hierarchy for speech related tasks and Ding et al (2016) demonstrated that, during listening to connected speech, cortical activity of different timescales concurrently tracked the time course of abstract linguistic compositionality at different hierarchical levels, such as words, phrases and sentences. In this work, we propose a character-level recurrent neural network (RNN) LM that employs an adaptive multiple timescales approach to incorporate temporal hierarchies in the architecture to enhance the representation of multiple compositionalities.…”
Section: Introductionmentioning
confidence: 99%
“…These self-organised values are then transferred to the EC layer and associated with the present embodied perception (EI layer). For training the MTRNN we use an adaptive variant of the real-time backpropagation through time (RTBPTT) algorithm [22,45].…”
Section: Learningmentioning
confidence: 99%
“…Compared to the previous ICANN contribution [23], the results are based on twice the number of runs per setup and per experiment. The parameters of the network and the metaparameters were mostly chosen based on the experience in [22] and [25] and are detailed in Tab 1. The number of neurons in the input layers |I IO | and |I EC | are given by the input representations.…”
Section: Evaluation and Analysismentioning
confidence: 99%
“…These self-organised values are then transferred to the EC layer and associated with the present embodied perception. For training we use an adaptive mechanism based on the resilient propagation algorithm [8]. During testing, the system approximates EC values from the visual perception input that are transferred to the Csc units, which in turn initiate the generation of a corresponding verbal utterance.…”
Section: Extended Mtrnn Modelmentioning
confidence: 99%